2011
DOI: 10.1016/j.ejcts.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Single-lung transplantation: does side matter?

Abstract: The preferred side for SLTx differed between fibrotic versus emphysema recipients. Transplant side does not influence recipient survival, freedom from BOS, complications, or pulmonary function after SLTx. Besides surgical considerations in the recipient, offer of a donor lung opposite to the preferred side should not be a reason to postpone the transplantation until a better-matched donor is found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In contrast to SSLTx, SLT recipients are more likely to experience pneumothorax, hyperinflation, and opportunistic infections, especially with Mycobacterium species and Aspergillus associated with native lung. Therefore, this can potentially compromise both early and late outcomes[ 58 , 60 ].…”
Section: Native Lung Complicationsmentioning
confidence: 99%
“…In contrast to SSLTx, SLT recipients are more likely to experience pneumothorax, hyperinflation, and opportunistic infections, especially with Mycobacterium species and Aspergillus associated with native lung. Therefore, this can potentially compromise both early and late outcomes[ 58 , 60 ].…”
Section: Native Lung Complicationsmentioning
confidence: 99%
“…Since the native lung on the severe side is more dysfunctional, it would not be unreasonable to choose that side for transplantation. However, Tsagkaropoulos et al reported that the transplant side does not influence recipient survival, freedom from bronchiolitis obliterans, complications, or pulmonary function after SLT [ 83 ]. Besides surgical considerations in the recipient, the offer of a donor lung opposite to the preferred side should not be a reason to postpone the transplantation until a better-matched donor is found [ 83 ].…”
Section: Size Matchingmentioning
confidence: 99%